2013
DOI: 10.1017/s1463423613000339
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ experience of being triaged directly to a psychologist in primary care: a qualitative study

Abstract: BackgroundIn a primary health-care centre (PHCC) situated in a segregated area with low socio-economic status, ‘primary care triage’ has increased efficiency and accessibility. In the primary-care triage, the nurse sorts the patient to the appropriate PHCC profession according to described symptoms.AimThe aim of this study was to examine the patients’ experience of being triaged directly to a psychologist for assessment.MethodInterviews were conducted with 20 patients and then analysed using qualitative conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…When MHT tools are applied in primary care, patients report increased satisfaction due to perceived improved accessibility to care and greater determination over treatment (Dahlöf et al . 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When MHT tools are applied in primary care, patients report increased satisfaction due to perceived improved accessibility to care and greater determination over treatment (Dahlöf et al . 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In nonemergency settings, such as community clinics, the application of MHT tools may be associated with reduced wait times and improved outcomes (depression scores; Smith & Hadorn 2002, Tulloch et al 2018. When MHT tools are applied in primary care, patients report increased satisfaction due to perceived improved accessibility to care and greater determination over treatment (Dahl€ of et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A special sorting manual was developed for this purpose in order to standardize the procedure and physiotherapists, psychologists and occupational therapists started to treat patients with certain conditions triaged directly to them by the nurses without a referral from a general practitioner [ 15 ]. Follow-up studies showed that the structured patient-sorting system seemed to satisfy the patient’s wish and need for quick access to a psychologist and that long-term healthcare consumption decreased for patients initially seeing physiotherapists [ 18 , 19 ]. The structured patient-sorting system has been adopted by a number of primary care centres in Sweden.…”
Section: Methodsmentioning
confidence: 99%
“…Assessors that demonstrated warmth, respect and non-judgemental attitudes and a flexible approach tailored to individual needs were experienced positively (Boscarato et al, 2014;Dahlöf et al, 2014;Hamilton et al, 2011;Meehan et al, 2012). Additionally, assessments that were person-centred, dynamic and receptive to modification as service users provided further information or as their needs changed were experienced more positively allowing individuals to feel more relaxed, comfortable, involved and empowered (Danna, 2011;McDonagh, 1997).…”
Section: Interpersonal Qualities Skills and Holistic Approachesmentioning
confidence: 99%